Cover Feature: d/f‐Polypnictides Derived by Non‐Classical Ln2+ Compounds: Synthesis, Small Molecule Activation and Optical Properties (Chem. Eur. J. 29/2021). Issue 29 (10th May 2021) - Reinfandt, Niklas; Michenfelder, Nadine; Schoo, Christoph; Yadav, Ravi; Reichl, Stephan; Konchenko, Sergey N.; Unterreiner, Andreas N.; Scheer, Manfred; Roesky, Peter W.
Abstract : A building site for the construction of novel df‐polypnictides by means of reduction with non‐classical divalent lanthanide compounds is depicted in the cover image. The poster on the right shows the target compound that is currently being assembled from the individual components. The building site is commissioned by fs‐Investigations GmbH for further femto‐second spectroscopic investigations of the compounds. More information can be found in the Full Paper by P. W. Roesky et al. (DOI: 10.1002/chem.202100605 ).